The evolution of muqarnas in Iran from pre-seljuk to ilkhanid period - Kazempourfard, Hamidreza (2014)
Muqarnas has always been one of the most complex decorative elements of worlds monumental architecture. In muqarnas, niche–like components are combined together and arranged in successive tiers to produce a three–dimensional geometric shape, enclosing and embellishing features such as ceiling, soffit, portal, and vault. This unique structure has been intensely studied from various aspects by many scholars. Nevertheless, there is still lack of clarification about the structures origin and path of evolution. There are some theories indicating that the structure is originated from squinches in Iran, but no further explanation is provided to fill the huge gap between the two, i.e. muqarnas and squinch, and to clarify the quality of the gradual development. This study assumes that the missing link between muqarnas and squinch should be sought in another undefined form in traditional architecture of Iran, named patkaneh. In this research, the main effort is to investigate the possibility of differentiating this ornament from muqarnas and to introduce it as a different structure, which is the missing link between squinch and muqarnas. This thesis employs a qualitative approach that strives to demonstrate the steps of gradual deformation of muqarnas from squinch by defining the characteristics of the linking ornament, using an inductive approach. For that, 20 critical samples of muqarnas and pseudo-muqarnas were selected out of a collection of 100 structures, by considering three main perspectives, i.e. chronology, form and structure, and construction techniques, with specific attention to the structure?s constituent elements and number of tiers as an indicator of the ornaments complexity. The differences and similarities identified among the selected samples lead to demonstrating the structures path of evolution. The results show there is another type (patkaneh) of ornamental structures with different characteristics in comparison with muqarnas. Therefore, this study contributes patkaneh as the connecting link between muqarnas and squinch, which is misinterpreted in many texts as muqarnas and thereafter shall be appropriately referred to none other than patkaneh.